2006
DOI: 10.1002/crat.200610747
|View full text |Cite
|
Sign up to set email alerts
|

Optical phonon modes and transmissivity in BaWO4 single crystal

Abstract: Barium tungstate (BaWO 4 ) single crystal has been grown using Czochralski technique. It belongs to the scheelite structure, forming the space group I4 1 /a at room temperature and the primitive cell contains two molecular units. The polarized Raman spectra were recorded by a micro-Raman spectrophotometer system in the backscattering geometry. All the observed Raman modes were assigned. The Raman mode at 924 cm -1 , which belongs to the totally symmetrical A g optical modes, has the strongest intensity and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…The presence of the Urbach's tail is in agreement with the conclusion drawn from low-temperature measurements performed by Itoh et al [12]. These authors as well as others also concluded that the lowest band-gap of metal tungstates is direct [12,14,19]. This result is also supported by recent electronic-structure calculations [21,30] and contradicts the apparent indirect character assigned to the lowest band-gap of CaWO 4 and SrWO 4 by Arora et al [10].…”
Section: Resultssupporting
confidence: 86%
“…The presence of the Urbach's tail is in agreement with the conclusion drawn from low-temperature measurements performed by Itoh et al [12]. These authors as well as others also concluded that the lowest band-gap of metal tungstates is direct [12,14,19]. This result is also supported by recent electronic-structure calculations [21,30] and contradicts the apparent indirect character assigned to the lowest band-gap of CaWO 4 and SrWO 4 by Arora et al [10].…”
Section: Resultssupporting
confidence: 86%
“…Figure 2 shows the spectral information of the Raman laser, which was recorded at an incident pump power of 15.2 W. It can be seen that the fundamental laser emission was at 1.94 μm and the first Stokes component was at 2.36 μm. We can see that the frequency shift of the fundamental laser and the first Stokes component was 924 cm −1 , which was in agreement with the Raman frequency shift of the a-cut BaWO 4 crystal reported in [22,25]. In this experiment, the second Stokes component was not observed at the maximum Raman output power.…”
Section: Resultssupporting
confidence: 91%
“…BaWO 4 crystals belong to scheelite-type tetragonal structures with a space group of (I4 1 /a), a point-group symmetry of (C 6 4h ) and four molecular formula per unit cell (Z = 4). 60 Fig. 3(a) shows that bonds between O-W-O and O-Ba-O atoms were projected out of the unit cell.…”
Section: Resultsmentioning
confidence: 99%